Emerging Insights into the Relationship Between Amino Acid Metabolism and Diabetic Cardiomyopathy - Yi Wen; Xiaozhu Ma; Shuai Mei; Qidamugai Wuyun; Jiangtao Yan (Biomolecules)
Diabetes mellitus (DM) is a complex global pandemic that frequently leads to multiple complications. Diabetic cardiomyopathy (DCM) is the primary cause of heart failure in patients with type 1 and 2 diabetes and is fundamentally characterized by abnormalities in myocardial structure and function. Metabolic disorders occupy a leading role in the pathogenesis of DCM, manifesting as disrupted substrate metabolism, dysregulated signaling pathways, and energy imbalance. Given the limited benefits of conventional therapeutic strategies targeting glucolipid metabolism, increasing research efforts have focused on amino acid metabolism. Amino acids are involved in the synthesis of nitrogen-containing compounds and serve as an energy source under specific conditions. Moreover, emerging studies demonstrate that metabolic disturbances of specific amino acids—such as branched-chain amino acids (BCAAs), glutamine, and arginine—exacerbate mitochondrial dysfunction and oxidative stress, thereby promoting myocardial fibrosis and cardiomyocyte injury. Therefore, this review aims to summarize the general characteristics and regulatory pathways of amino acid metabolism, as well as the specific mechanisms by which metabolic alterations of amino acids contribute to the pathogenesis and progression of diabetic cardiomyopathy, with the hope of advancing more effective translational therapeutic approaches.